Facilitating Learning at Home: The Experiences of Parents With Multiple Children - Cruz, Sahara Theresa; Guzman, Judelyn De; Silva, Liezle De; Borja, Joanna Marie de (FKIP Universitas Lampung, 2021)
Facilitating Learning at Home: The Experiences of Parents with Multiple Children. Objectives: The study explored the experiences of parents who are assisting multiple children in accomplishing learning tasks. Methods: The study employed a phenomenological research design using semi-structured interviews. Ten parents were purposefully selected to participate in the study. All of them are female and working mothers. The data were analyzed using thematic analysis. Findings: The gathered data and analysis of the findings identified five emerging themes capped into FOCUS (Facilitating learning tasks, Older siblings help, Challenging and lack of confidence, Understanding, and Safety and security) describing parents with multiple children experiences in time of pandemic. Conclusions: One conclusion states that parents’ lack of skills and expertise regarding how to teach their children is one of the most challenging aspects.Keywords: distance learning modality, facilitators, parents with multiple children, lived experiences, challenges.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202119